2008
DOI: 10.1097/sla.0b013e318153ff40
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Recurrence Rate After Negative Sentinel Node Biopsy in Breast Cancer

Abstract: This is the first report from a national multicenter study that covers, not only highly specialized institutions but also small community hospitals with just a few procedures per year. Despite this heterogeneous background, the results lie well within the range of AR rates published internationally (0%-3.6%). The sentinel node biopsy procedure seems to be safe in a multicenter setting. Nevertheless, long-term follow-up data should be awaited before firm conclusions are drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 35 publications
3
33
0
2
Order By: Relevance
“…Langer et al [34] revealed 96% of patients with ITC from SLN biopsy undergoing delayed ALND to have specimens free of macro-metastases and without benefit of ALND. SLN ITCpositive patients who did not receive ALND were shown to have a relapse rate between 0 and 3.6% [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Langer et al [34] revealed 96% of patients with ITC from SLN biopsy undergoing delayed ALND to have specimens free of macro-metastases and without benefit of ALND. SLN ITCpositive patients who did not receive ALND were shown to have a relapse rate between 0 and 3.6% [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…15 Table 3 summarizes the recurrence rates of publications with at least 500 patients. [14][15][16][17][18][19][20][21][22] An interesting note should be made of the meta-analysis in that only one paper had follow-up longer than 5 years (65 months). 23 The recurrence rate in this group was higher than in a majority of the papers published in the past (2.68%).…”
Section: P-valuementioning
confidence: 99%
“…The axillary surgery, either by axillary lymph-node dissection (ALND) or by sentinel lymph-node dissection is an important procedure in the surgical treatment of breast cancer, allowing a prognostic purpose, reducing recurrence and contributing to plan an appropriate adjuvant therapy program [1][2][3][4][5]. Axillary surgery also has post-operative morbidity including early and long term complications as bleeding, infection at the operation site, axillary web syndrome (AWS), arm or shoulder weakness and motion restriction, swelling, numbness, pain and lymphedema [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%